Potential Types of Plants as Food Sources In Galela Coastal Community - Ariance Yeane Kastanja; Zeth Patty; Zakarias Dilago (Sangia Publishing, 2020)
The objectives of this study are 1). Knowing the types of plants that have the potential as a food source 2) Knowing which parts of plants are used as foodstuffs 3) Knowing how to process plant species as a source of food for the people on the coast of Galela, while the benefit of this research is the identification of plant types that have the potential to be a source of food for the community galela area. The method used is a survey method by giving structured questions. Primary data is data from interviews with respondents and direct observation in the field, which includes; observation data on plant species, (2) parts of the plant used (3) how to process the food material. Respondents in this study were housewives in the coastal area of Galela with a total of 65 respondents. The results showed that 1) there were 35 types of plants and 20 families that were used by the community as food sources, both cultivated and found in nature. The parts of plants consumed by the community vary, ranging from leaves, stems, flowers, fruit, tubers, rhizomes, to leaf buds. The leaves, flowers, young stems are mostly consumed as vegetables. 3) The types of bananas and yams consumed as staple food are usually processed by boiling, coconut milk, or frying them.